Parasite-induced anorexia and its association with the immune response and plasma leptin concentrations in lambs of two genotypes - Zaralis K.; Tolkamp B.J.; Wylie A.R.G.; Houdijk J.G.M.; Stear M.; Kyriazakis I. (Challenging strategies to promote the sheep and goat sector in the current global context, 2011)
The degree of anorexia (i.e. reduction in voluntary food intake) in lambs following nematode infection may be sensitive to host production potential. An increase in plasma leptin concentrations (PLC) following infection may be related to the occurrence of anorexia. Our study tested the hypotheses that (i) the degree of anorexia will be greater in parasitized lambs selected more intensively for growth, and (ii) nematode infection will increase PLC in lambs. In Experiment I, 48 Suffolk x Greyface (S) and 48 Scottish Blackface (B) were used. Half lambs of each genotype were infected with the nematode Teladorsagia circumcincta and fed ad libitum. The remaining were not infected and either fed ad libitum or pair-fed to infected lambs. In Experiment II, previously infected lambs were either not re-infected or re-infected 4- or 8-weeks after the end of the primary infection. S lambs were more susceptible to infection than B lambs, as shown by faecal egg counts and IgA results in Experiment I. A mild anorexia was observed in both S and B lambs during the primary infection only. Neither primary nor secondary infections lead to an increase in PLC. Our data suggest that differences in intrinsic capacity for growth in lambs are associated with differences in the ability to cope with infection. Leptin seems unlikely to be responsible for T. circumcincta-induced anorexia.
13. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2009/10/14-16, León (Spain)